Disgusto e femminilità in Atterraggio di emergenza di Shulamit Lapid (Altre Modernità, 2014)
In her "From Disgust to Humanity. Sexual Orientation & Constitutional Law", Martha Nussbaum deals with the concept of ‘disgust’ in the human culture. According to Nussbaum, ‘Disgust’ is the reaction to the problematic relationship between the human being, his animal nature and his mortality. ‘Projective disgust’ consists in projecting man’s “disgusting nature” onto particular social groups or human categories, to create a sort of boundary mark between ‘Man’s Purity’ and the ‘Disgust’. This boundary mark is, first, occupied by Woman and, after, by individuals considered “like women” (homosexuals, Jews…). This essay applies Martha Nussbaum’s theories to a short story by Shulamit Lapid, an Israeli writer. In her "Nekhitat Ones" (“emergency landing”), the author represents a rape acted by a woman to a man who, for the disgust provoked by this traumatic experience, probably dies. The opposition between femininity and masculinity is exasperated; presenting a ‘rape at the contrary’, Shulamit Lapid makes the reader feel the horror connected to this terrible act and discusses the question of disgust as a cultural and a social mark.